Test and finite element analysis of gravity load designed precast concrete wall under reversed cyclic loads - Preeda Chaimahawan (2018)
© 2018, Chulalongkorn University. All rights reserved. This research studies the lateral behavior of precast concrete wall panel applicable for a 2-story building. The specimens consist of precast and cast in-situ reinforced concrete bearing wall with 3/4 scaled. The precast wall panel was designed for gravity load only. The specific connection in this study was the welded connection between dowel bar and steel plate embedded in precast wall which was the famous one of the connection for precast bearing wall system in Thailand. The specimens are tested under reversed cyclic loadings through hydraulic actuator in laboratory. The tested results reveal that the precast concrete wall can resist maximum lateral load and show almost the same behavior as cast in-situ RC wall. The cracks of precast wall panel are concentrated around the connection while cast in-situ RC wall are flexural and shear cracks dominant 500 millimeters above the footing of wall. The superimposed technique of the element in FEM analysis is used to model the connection of precast wall. The prediction by FEM analysis for cyclic behavior, hysteretic loop and maximum load are matched with the test results for both specimens.